The Number of Metastatic Lymph Nodes is a Useful Predictive Factor for Recurrence after Surgery for Nonmetastatic Nonfunctional Neuroendocrine Neoplasm of the Pancreas - G. Capretti; G. Nappo; V. Smiroldo; M. Cereda; B. Branciforte; P. Spaggiari; S. Carrara; P. Preatoni; F. Gavazzi; C. Ridolfi; G. Donisi; A. Lania; et al. (Gastroenterology Research and Practice)
Nodal involvement (actually categorized as positive or negative) is an important prognostic factor after surgery for pancreatic neuroendocrine neoplasms (pNENs). We aim to evaluate the predictive role of the number of nodal metastases after pancreatic resection for pNENs. We analyzed from a prospectively maintained database all pancreatic resections for nonmetastatic nonfunctioning pNENs performed in our institution from 2011 to 2016. According to the number of nodal metastases, enhancing the actual categorization, we distinguished the following: N0, no nodal metastases; N1, 1-3 metastatic lymph nodes; and N2, metastases in 4 or more regional lymph nodes. Recurrence and disease-free survival (DFS) were evaluated. The predictive value in terms of recurrence for each clinicopathological data, including the number of metastatic lymph nodes, was calculated. Univariate and multivariate analyses were conducted. 77 patients underwent pancreatic surgery for pNENs. N0, N1, and N2 resections were found in 52 (67.5%), 16 (20.8%), and 9 (11.7%) cases, respectively. Mean follow-up of the entire cohort was 48 (±25) months. The recurrence rate was 11.8%, and the mean time of recurrence was 12 (±14) months. DFS was 83.7 months (76.0 - 91.5). At a univariate analysis, factors associated with recurrence were mitotic count (OR 1.19, p=0.001), Ki67 value (OR 1.06, p=0.001), the presence of nodal metastases (OR 11.54, p=0.002), and metastases in 4 or more regional lymph nodes (N2) (OR 30.19, p=0.002). At a multivariate analysis, only mitotic count (OR 1.51, p=0.005) and N2 resection (OR 134.74, p=0.002) were found to be predictive factors of recurrence. The number of metastatic lymph nodes and mitotic count is the most significant predictive factors of recurrence after pancreatic surgery for nonmetastatic nonfunctioning pNENs.